2002
DOI: 10.1046/j.0960-7412.2001.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Double mutation cpSRP43/cpSRP54is necessary to abolish the cpSRP pathway required for thylakoid targeting of the light‐harvesting chlorophyll proteins

Abstract: SummaryBiochemical and genetic studies have established that the light-harvesting chlorophyll proteins (LHCPs) of the photosystems use the cpSRP (chloroplast signal recognition particle) pathway for their targeting to thylakoids. Previous analyses of single cpSRP mutants, chaos and ffc, de®cient in cpSRP43 and cpSRP54, respectively, have revealed that half of the LHCPs are still integrated into the thylakoid membranes. Surprisingly, the effects of both mutations are additive in the double mutant ffc/chaos desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 59 publications
(112 reference statements)
8
79
0
Order By: Relevance
“…The PSI and PSII core subunits PsaA/B, D2 and CP47 were reduced to about 50% of wild-type levels, whereas the levels of OE33, Cytf of Cytb 6 /f and the β-subunit of ATP synthase were unchanged compared with wild type. A previous report suggested that depletion of LHCP might result in impaired stability of photosynthetic proteins 29 . Pulse labelling for 20 min followed by a chase with unlabelled methionine in the presence of cycloheximide, which blocks the synthesis of nuclear-encoded proteins, showed that the turnover rates of the PSI and PSII subunits (PsaA/B, CP47, CP43, D1 and D2) were higher in ltd than in wild-type plants ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PSI and PSII core subunits PsaA/B, D2 and CP47 were reduced to about 50% of wild-type levels, whereas the levels of OE33, Cytf of Cytb 6 /f and the β-subunit of ATP synthase were unchanged compared with wild type. A previous report suggested that depletion of LHCP might result in impaired stability of photosynthetic proteins 29 . Pulse labelling for 20 min followed by a chase with unlabelled methionine in the presence of cycloheximide, which blocks the synthesis of nuclear-encoded proteins, showed that the turnover rates of the PSI and PSII subunits (PsaA/B, CP47, CP43, D1 and D2) were higher in ltd than in wild-type plants ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Input, 4% of the prey protein. pigment deficiency phenotypes 16,21,23,28,29,34 . The ltd mutant did not develop any fertile flowers (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in components of a secondary destination translocase (e.g. the thylakoid translocases; Li et al, 1995;Voelker and Barkan, 1995;Hutin et al, 2002;Martin et al, 2009) generally have effects limited to that compartment. Although SEC2 can be considered a destination translocase, reduced SCY2 expression through Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane insertion of the LHCPs strictly requires cpFtsY, GTP, and the integral membrane protein Alb3 in vitro (Tu et al, 1999;Moore et al, 2000Moore et al, , 2003. However, disruption of the genes encoding cpSRP54 and cpSRP43 in Arabidopsis thaliana has only mild effects on the accumulation of LHCPs in comparison with the wild type, whereas the disruption of Alb3p leads to a loss of LHCPs (Sundberg et al, 1997;Tu et al, 1999;Hutin et al, 2002). This suggests the existence of an alternative insertion pathway of LHCPs into the thylakoid membrane and/or additional functions of the mutated factors in vivo.…”
Section: Introductionmentioning
confidence: 99%